Analytical Indicators of the Middle-Income Population in Uzbekistan - Khasankhonova Nodira Isametdinovna (Researchparks Publishing, 2022)
One of the factors influencing the efficient use of labor resources and changing its level is the income of the middle-income population. This article examines the economic analysis of the middle-income population in Uzbekistan. The article analyzes the share of the poor, the income of the population by the detsel ratio.